1974
DOI: 10.2307/1238602
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Test of Utility vs. Profit Maximization in Agricultural Production

Abstract: Production economics literature contains many studies which assume that the producer's goal is to ma,cimize profits. This study tests the hypothesis that Bernoullian and le,cicographic utility are more accurate predictors of farmer behavior than profit maximization. Si,c large California farms were used to test the hypothesis. After-income ta,c E-V (e,cpectation-variance) boundaries were developed for each farm and utility, and profit maximizing crop plans were determined for each. A goodness-of-fit criterion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0
3

Year Published

1990
1990
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(79 citation statements)
references
References 11 publications
2
73
0
3
Order By: Relevance
“…Experiments and hypothetical alternatives are usually used to determine risk aversion using this method. This approach was used by Offi cer and Halter (1968), Lin et al (1974), Webster and Kennedy (1975), Dillon and Scandizzo (1978), Halter and Mason (1978), Young (1979) and Collins et al (1991). The second approach stands on a position that risk aversion is a latent feature and can be observed only indirectly (for example through observing farmers' investment activities).…”
Section: Risk Perception and Risk Aversion Among Farmersmentioning
confidence: 99%
“…Experiments and hypothetical alternatives are usually used to determine risk aversion using this method. This approach was used by Offi cer and Halter (1968), Lin et al (1974), Webster and Kennedy (1975), Dillon and Scandizzo (1978), Halter and Mason (1978), Young (1979) and Collins et al (1991). The second approach stands on a position that risk aversion is a latent feature and can be observed only indirectly (for example through observing farmers' investment activities).…”
Section: Risk Perception and Risk Aversion Among Farmersmentioning
confidence: 99%
“…The results indicated that the Ramsey model was superior to the Von NeumannMorgenstern models. Lin, Dean and Moore (1974) provided an empirical test for utility vs. profit maximization in agricultural production in California. Utility and profit maximization crops and plans were determined for six large California farms.…”
Section: Independencementioning
confidence: 99%
“…The suggestion of the Lin et al [1974] study and of earlier studies [officer and Halter, 1968;Dillon and Anderson, 1971;and Massell and Johnson, 1968] is that farm decision makers act as utility maximizers rather than profit maximizers. Utility can be defined as a function of "returns" and "risks"; more specifically, a function of expected returns such that U = F(R, a^) (3.1) and…”
Section: Specification Of the Objective Functionmentioning
confidence: 99%
“…In a study of six large California farms, Lin et [1974] concluded that farmer behavior is more accurately explained by utility maximization (specifically, Bemoullian utility) than by profit maximization. Using the chi-square goodness-of-fit criterion as their measure, the authors showed that the Bemoullian utility formulation provided the most accurate prediction of actual cropping patterns among the six farms included in the study.^ Their hypothesis was that farmer attitude toward risk is the factor which contributes most to the discrepancy between actual optimizing behavior and that predicted by profit maximizing ^The chi-square goodness-of-fit test compares the postulated probability distribution with that suggested by the data to determine whether they are, in fact, the same.…”
Section: Specification Of the Objective Functionmentioning
confidence: 99%
See 1 more Smart Citation